Pelayanan Swamedikasi Metampiron di Beberapa Apotek Kabupaten Jombang (Studi Dengan Metode Simulasi Pasien) - Sifa Nisa; Adinugraha Amarullah; Khurin In Wahyuni (Program Studi Farmasi Fakultas Sains Kesehatan, 2021)
Pharmaceutical services are activities carried out by pharmacists for patients in improving the quality of life of patients. There are many pharmaceutical services, one of which is self-medication. . One of the drugs that can be used for self-medication is metampirone. The stages of self-medication are patient assessment, determination of recommendations, drug delivery and information provision. This study aims to determine a self-medication service for methampyrone in several pharmacies in Jombang district using the patient simulation method. The technique in this research is descriptive using purposive sampling method, with a population of 82 pharmacies obtained a sample of 45 pharmacies. The instruments used are research protocols, scenarios and checklists. Results obtained at the patient assessment only 4 (8.89%) pharmacy do,stage of determining the recommendations there are 45 (100%) pharmacy do. And on results of providing information there are 1 (2.22%) pharmacy do.